Urinary level of 1,2-dichloroethane and its effects on blood biochemical markers among outdoor workers exposed to air pollution in Thailand - Thetkathuek, Anamai; Kongsombatsuk, Marissa; Nakyai, Teeranun; Polyong, Chan P. (Narra J, 2024)
Air contamination by 1,2-dichloroethane (1,2-DCE) is recognized as a threat across countries. Addressing this problem is challenging due to the absence of clearly defined biological standards for monitoring 1,2-DCE exposure among humans. Moreover, studies on the impacts of 1,2-DCE exposure on human health are limited. The aim of this study was to determine the level of 1,2-DCE in urine—separated into the health behavior and occupation groups—as well as its effects on blood biochemicals among overall 200 outdoor workers, with 50 working in each of the following four occupations: fishers, street vendors, public bus drivers, and traffic police in an environmentally polluted community in Thailand. The subject’s behaviors were categorized into four groups: desirable health behaviors (non-smokers and non-drinkers), non-smokers who consume alcohol, smokers who do not consume alcohol, and undesirable health behaviors (frequent smokers and alcohol consumers). Data were collected at the end of the workday using interview forms, urine, and blood samples. Urine was analyzed for 1,2-DCE, and blood was analyzed for complete blood count (CBC), liver, and kidney function enzymes. Data were analyzed using the Dunnett’s test, Kruskal-Wallis H test, and independent sample t-test according to statistical conditions. Our findings revealed that the median urinary 1,2-DCE level was 0.080 mg/L (0.022–0.462 mg/L). Subjects with undesirable health behaviors had a significantly higher urinary 1,2-DCE level (0.108 mg/L) compared to those with desirable health behaviors (0.056 mg/L), with a p-value of 0.009. Among bus drivers and local fishers, the dose of exposure was strongly associated with creatinine levels (p=0.006). No significant association was observed between exposure dose and CBC across all groups. In conclusion, the urinary samples present a small variation in 1,2-DCE concentrations and thus can be used as a benchmark baseline value for monitoring exposure among outdoor workers in areas with intense air pollution. Kidney function markers can be considered in monitoring the health effects of 1,2-DCE.